Controlled-Release Oxycodone as “Gold Standard” for Postoperative Pain Therapy in Patients Undergoing Video-Assisted Thoracic Surgery or Thoracoscopy: A Retrospective Evaluation of 788 Cases - Kampe, Sandra; Weinreich, Gerhard; Darr, Christopher; Stamatis, Georgios; Hachenberg, Thomas (The Thoracic and Cardiovascular Surgeon, 2015)
Background To assess the clinical efficacy of controlled-release oxycodone for postoperative analgesia after video-assisted thoracic surgery (VATS) or thoracoscopy.Methods Pain therapy is standardized in our thoracic center throughout the complete postoperative stay. Patients receive immediately postoperative standardized oral analgesic protocol with controlled-released oxycodone (Oxy Group) or oxycodone with naloxone (Targin Group) and nonopioid every 6 h. We switched the opioid protocol from controlled-release oxycodone to Targin in January 2012. All patients are visited daily by a pain specialist throughout the whole stay.Results Data of 788 patients undergoing VATS (n = 367) or thoracoscopy (n = 421) during January 2011 until March 2013 were analyzed. In VATS, patients with Targin had higher pain scores at rest (p < 0.02) and on coughing (p < 0.001) than patients with oxycodone alone and more patients with Targin were dismissed with oral opioid dose than patients with oxycodone alone (p < 0.001). No differences in pain scores on POD 5 and 6, or in length of hospital stay, incidence of nausea, time to first dejection or opioid dose after dismission were found between controlled-release oxycodone and Targin. After conventional thoracoscopy, 209 patients received controlled-release oxycodone and 212 Targin. Patients with Targin had higher pain scores at rest (p < 0.004) and on coughing (p < 0.01) than patients with oxycodone alone and more patients with Targin were dismissed with oral opioid dose than patients with oxycodone alone (p < 0.004). There were no differences in pain scores on POD 5 and 6, or in length of hospital stay, incidence of nausea, time to first dejection or opioid dose after dismission.Conclusion Oral opioid analgesia with controlled-release oxycodone is an effective postoperative regimen after VATS and thoracoscopies. Our retrospective data indicate that Targin might be less effective analgesic than oxycodone after VATS and thoracoscopies with no improvement in bowel function in the immediate postoperative period.Study Limitations The study design is retrospective in nature.
Keywords: postoperative pain therapy; VATS; thoracoscopy; gold standard; oral opioids; length of hospital stay; recovery of bowel function